A review of the clinical applications of drug delivery systems for the treatment of ocular anterior segment inflammation. Issue 12 (30th October 2020) - Wong, Chee Wai; Metselaar, Josbert M; Storm, Gert; Wong, Tina T
Abstract : Ocular anterior segment inflammation is a medical problem that is seen in cases of cataract surgery and non-infectious anterior uveitis. Inadequately treated anterior segment inflammation can lead to sight-threatening conditions such as corneal oedema, glaucoma and cystoid macular oedema. The mainstay of treatment for anterior segment inflammation is topical steroid eye-drops. However, several drawbacks limit the critical value of this treatment, including low bioavailability, poor patient compliance, relatively difficult administration manner and risk of blurring of vision and ocular irritation. A drug delivery system (DDS) that can provide increased bioavailability and sustained delivery while being specifically targeted towards inflamed ocular tissue can potentially replace daily eye-drops as the gold standard for management of anterior segment inflammation. The various DDS for anti-inflammatory drugs for the treatment of anterior segment inflammation are listed and summarised in this review, with a focus on commercially available products and those in clinical trials. Dextenza, INVELTYS, Dexycu and Bromsite are examples of DDS that have enjoyed success in clinical trials leading to FDA approval. Nanoparticles and ocular iontophoresis form the next wave of DDS that have the potential to replace topical steroids eye-drops as the treatment of choice for anterior segment inflammation. With the current relentless pace of ophthalmic drug delivery research, the pursuit of a new standard of treatment that eliminates the problems of low bioavailability and patient compliance may soon be realised.